2015
DOI: 10.1016/j.jphys.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation that incorporates virtual reality is more effective than standard rehabilitation for improving walking speed, balance and mobility after stroke: a systematic review

Abstract: Substituting some or all of a standard rehabilitation regimen with VRBR elicits greater benefits in walking speed, balance and mobility in people with stroke. Although the benefits are small, the extra cost of applying virtual reality to standard rehabilitation is also small, especially when spread over many patients in a clinic. Adding extra VRBR time to standard rehabilitation also has some benefits; further research is needed to determine if these benefits are clinically worthwhile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
185
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(225 citation statements)
references
References 55 publications
11
185
0
6
Order By: Relevance
“…[108][109][110] These therapies can improve upper limb function, walking speed, balance, and mobility in people with stroke by enhancing traditional poststroke treatment through simulated practice of therapy-related tasks at a higher dose, for longer periods, consistently and precisely without fatigue. [110][111][112][113] However, because of the lack of high-quality evidence, both clinical and costeffectiveness, the benefits and risks of robotic, virtual reality, and gaming-based rehabilitation compared with conventional therapies remain unclear. [112][113][114][115] Large, welldesigned, multicenter studies evaluating the benefits and risks of robotic, virtual reality, and gaming therapy are clearly needed.…”
Section: Telerehabilitation Via Robotic Virtual Reality and Gaming-mentioning
confidence: 99%
See 1 more Smart Citation
“…[108][109][110] These therapies can improve upper limb function, walking speed, balance, and mobility in people with stroke by enhancing traditional poststroke treatment through simulated practice of therapy-related tasks at a higher dose, for longer periods, consistently and precisely without fatigue. [110][111][112][113] However, because of the lack of high-quality evidence, both clinical and costeffectiveness, the benefits and risks of robotic, virtual reality, and gaming-based rehabilitation compared with conventional therapies remain unclear. [112][113][114][115] Large, welldesigned, multicenter studies evaluating the benefits and risks of robotic, virtual reality, and gaming therapy are clearly needed.…”
Section: Telerehabilitation Via Robotic Virtual Reality and Gaming-mentioning
confidence: 99%
“…[110][111][112][113] However, because of the lack of high-quality evidence, both clinical and costeffectiveness, the benefits and risks of robotic, virtual reality, and gaming-based rehabilitation compared with conventional therapies remain unclear. [112][113][114][115] Large, welldesigned, multicenter studies evaluating the benefits and risks of robotic, virtual reality, and gaming therapy are clearly needed. Research that provides information on optimal dose, appropriate time to initiate such therapies, and criteria for identifying patients who will benefit most from such therapies is especially needed.…”
Section: Telerehabilitation Via Robotic Virtual Reality and Gaming-mentioning
confidence: 99%
“…The authors reported significant improvements among those using VR compared to controls on the Berg Balance Scale (BBS) and the Timed Up and Go Test (TUG). Li et al, 7 among others, 8,9 positively assert the use of VR in the stroke population as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…A more recently published systematic review and meta-analysis investigating the use of virtual reality in a stroke population found that substitution of some or all of standard rehabilitation with virtual reality training resulted in improved mobility. 18 [ 2 4 _ T D $ D I F F ] However, when data were pooled from trials that used exergames as an addition to standard therapy, there was insufficient evidence of effect due to[ 2 5 _ T D $ D I F F ] a lack of trials that evaluated walking speed, and the heterogeneity of the participants. 18 The feasibility of exergame use in rehabilitation settings remains unclear, with one study suggesting that patients prefer traditional therapy.…”
mentioning
confidence: 99%
“…18 [ 2 4 _ T D $ D I F F ] However, when data were pooled from trials that used exergames as an addition to standard therapy, there was insufficient evidence of effect due to[ 2 5 _ T D $ D I F F ] a lack of trials that evaluated walking speed, and the heterogeneity of the participants. 18 The feasibility of exergame use in rehabilitation settings remains unclear, with one study suggesting that patients prefer traditional therapy. 19 More research is therefore required to evaluate the feasibility and impact of a range of different interactive video and computer systems to address mobility limitations in rehabilitation ward settings.…”
mentioning
confidence: 99%